2010
DOI: 10.1051/0004-6361/201014590
|View full text |Cite
|
Sign up to set email alerts
|

Herschelimages of NGC 6720: H2formation on dust grains

Abstract: Herschel PACS and SPIRE images have been obtained of NGC 6720 (the Ring nebula). This is an evolved planetary nebula with a central star that is currently on the cooling track, due to which the outer parts of the nebula are recombining. From the PACS and SPIRE images we conclude that there is a striking resemblance between the dust distribution and the H 2 emission, which appears to be observational evidence that H 2 forms on grain surfaces. We have developed a photoionization model of the nebula with the Clou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
(38 reference statements)
4
29
0
Order By: Relevance
“…Molecular hydrogen formation in the knots is expected to be substantial after the central star entered the cooling track and underwent a strong drop in luminosity, and may still be ongoing at this moment, depending on the density of the knots and the properties of the grains in the knots and assuming the knots formed quickly. Especially in the latter case we expect a tight correlation between the dust emission and the H 2 emission (van Hoof et al 2010) as is observed in the Helix nebula.…”
Section: Comparison With H 2 Imagesupporting
confidence: 66%
See 3 more Smart Citations
“…Molecular hydrogen formation in the knots is expected to be substantial after the central star entered the cooling track and underwent a strong drop in luminosity, and may still be ongoing at this moment, depending on the density of the knots and the properties of the grains in the knots and assuming the knots formed quickly. Especially in the latter case we expect a tight correlation between the dust emission and the H 2 emission (van Hoof et al 2010) as is observed in the Helix nebula.…”
Section: Comparison With H 2 Imagesupporting
confidence: 66%
“…Goldsmith (2001) found that for gas densities higher than 10 4.5 cm −3 the dust and gas temperatures will be closely coupled, also for temperatures as found in the Helix. It is another indication that, as is the case in the Ring Nebula (van Hoof et al 2010) andNGC 650 (van Hoof et al 2013), also in NGC 7293 H 2 and dust co-exist in these knots. This close correlation could be an indication of the formation of H 2 on dust grains.…”
Section: Comparison With H 2 Imagementioning
confidence: 82%
See 2 more Smart Citations
“…To further test the emission mechanisms contributing to the VVV bands, we made use of the published photo-ionisation model of van Hoof et al (2010) for NGC 6720, the Ring nebula. This is the archetypal planetary nebula; the nebula is bipolar, seen almost pole-on, optically thick to ionizing radiation except towards the poles.…”
Section: Sources Of 08−21 μM Emission In Planetary Nebulae In the Vmentioning
confidence: 99%